PENGARUH IMPLEMENTASI SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI (SAKTI), KOMPETENSI SUMBER DAYA MANUSIA DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH TINGKAT WILAYAH LINGKUP BADAN PUSAT STATISTIK - Hakim, Faraida; Kusumah, R. Wedi Rusmawan (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study examines the impact of the Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI), human resource competence, and internal control on the quality of government financial reports at the Central Bureau of Statistics (BPS). Using a quantitative approach with a causal research design, data were collected through questionnaires distributed to financial report preparers at BPS. Multiple linear regression analysis was conducted to test the research hypotheses. The findings indicate that the implementation of SAKTI, human resource competence, and the effectiveness of internal control have a positive and significant influence on financial report quality. Optimal implementation of SAKTI contributes to greater accuracy and transparency in financial reporting, while adequate human resource competence ensures precision in report preparation. Furthermore, an effective internal control system enhances compliance with regulations and prevents errors and fraud in financial reporting. These findings highlight the importance of strengthening human resource capacity, optimizing technology-based financial systems, and ensuring strict internal oversight to enhance government financial accountability.